PERAN BAHASA INDONESIA DALAM PROSES SOSIALISASI RADIKALISME DI SMAN 5 PEKANBARU - Ratu Husna Aulia; Nabila Ariyanda; Yuhelsa Marsanda; Tiara Syahfitri; Zahratul Alya Anwar; Zakia Aulia Zikra; Lexa Putri Amanda; Aufa Nur Asyifa; Ripi Hamdani (Jurnal Padamu Negeri, 2026)
The formal education system in Indonesia, from kindergarten to senior high/vocational schools, is not immune to the spread of radicalism. Education has become one of the "fertile grounds" for the cultivation of radicalism in the name of religion, ranging from classroom conversations, small group discussions, to textbooks that clearly illustrate these massive efforts. The socialization of radicalism aims to increase students' understanding of the dangers of radicalism. This education is carried out using socialization methods. The results of this activity show an increase in knowledge related to radicalism through strengthening media literacy and utilizing the Indonesian language as a means of uniting the nation.